The impact of COVID-19 on sport and daily activities in an Italian cohort of football school children - Farì, G.; Di Paolo, S.; Ungaro, D.; Luperto, G.; Farì, E.; Latino, F. (International Journal of Athletic Therapy & Training, 2021)
Background: Sport activities were interrupted due to a quarantine imposed to limit the spread of Coronavirus disease 2019 (COVID-19) in Italy. This study aimed to describe the impact of COVID-19 on sports and on daily activities in an Italian cohort of school children signed up in a football school. Methods: A total of 44 children from an Italian football school were enrolled. An online survey was distributed to these children and their parents in May 2020. The questionnaire collected information on the daily use of electronic devices and on the number of hours per week spent in activities regarding nonsport activities, highlighting the differences between those who interrupted sports and those who continued driven remotely by their instructors during the lockdown. Results: A total of 26 players continued practicing sports during the COVID-19 quarantine, while 18 players suspended their sports. Daily time spent on electronic devices increased significantly in both groups during the pandemic (p < .0001), regardless of whether they continued to practice sports (p > .05). On the other hand, in the group of children who interrupted sports, the time spent on activities regarding nonsport physical activity significantly changed during pandemic, with a 50% decrease (p = .0027) of those who spent more than 3 hr per week before the quarantine in favor of those who spent less than 3 hr per week. Conclusion: Quarantine increases screen time, which is a sedentary behavior that represents a risk factor for the health of children. Maintaining regular physical activity during quarantine due to COVID-19 was important to preserve some aspects of a healthy lifestyle in children, such as physical activity regardless of sport. While reducing physical activity and adapting it remotely, it is desirable that it be encouraged by experienced instructors in order to limit potential physical and psychological harm to children.